Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/jcm12123941
|View full text |Cite
|
Sign up to set email alerts
|

The Direct Anterior Approach (DAA) as a Standard Approach for Total Hip Arthroplasty (THA) in Coxa Profunda and Protrusio Acetabuli? A Radiographic Analysis of 188 Cases

Abstract: Introduction: The direct anterior approach (DAA) represents a well-recognized soft tissue sparing technique for primary total hip arthroplasty (THA). The feasibility and suitability of the DAA in cases of complex acetabular deformities, namely coxa profunda (CP) and protrusio acetabuli (PA), remain to be determined. Methods: A total of 188 cases of CP (100 cases) and PA (88 cases) hips undergoing primary THA via the DAA were retrospectively analyzed. Surgical and radiographic parameters were evaluated and pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…Heinz et al . 33 also showed that obese patients with acetabular protrusion may pose a significant limitation to the DAA. In this study, we found that 98.2% cup anteversion and 95.4% cup inclination in the Endo‐DAA group were inside the “safe zone.” While the rates of the cup anteversion outside of the “safe zone” were 24.1% and 17.7% in the Bikini DAA group and the conventional DAA group with significant differences compared to the Endo‐DAA group.…”
Section: Discussionmentioning
confidence: 94%
“…Heinz et al . 33 also showed that obese patients with acetabular protrusion may pose a significant limitation to the DAA. In this study, we found that 98.2% cup anteversion and 95.4% cup inclination in the Endo‐DAA group were inside the “safe zone.” While the rates of the cup anteversion outside of the “safe zone” were 24.1% and 17.7% in the Bikini DAA group and the conventional DAA group with significant differences compared to the Endo‐DAA group.…”
Section: Discussionmentioning
confidence: 94%
“…Correlating the radiographic findings with clinical data would have added additional strength to this study. So far, very limited studies have investigated the influence of BMI on cup positioning during DAA-THA [43,55]. Al-Amiry et al were the first to examine the association of BMI with leg-length discrepancy and femoral offset restoration [32].…”
Section: Discussionmentioning
confidence: 99%